An analysis of scientific evidences for design of an ideal herbal dental formulation - Sharma, Ravinder; Gupta, Vikas; Kaur, Gunpreet; Anubhav; Sharma, Pankaj; Garg, Meena (International Journal Of Community Medicine And Public Health, 2025)
This study is an analysis of components of herbal tooth pastes to highlight important dental herbs for the development of an ideal formulation with evidence-based approach. In this study ten herbal toothpaste formulations were purchased from the market, codified and the herbs present in all were tabulated. A comparison of their established pharmacological actions has been made. As per analysis the requirement of analgesics and anti-inflammatory agents is not a daily requirement and adds to a question mark for their inclusion in the daily use toothpaste. Some of the toothpastes have not included any herb but the product is being sold under the cover of herbal toothpaste demonstrating that OTC companies are just trying to en-cash the positive wave towards herbal formulations. Only 20% formulations are using astringent, 10% are using antiviral and only 30% are using anti-carcinogenic which is indeed needed for daily use in toothpaste. More than 30% toothpastes are using anti- allergic components and not justified as it may suppress the immune system. There is a need of revision of criteria for using selected herbs for better therapeutic activity.